Perancangan Struktur Pada Bangunan Bertingkat Menggunakan Metode Building Information Modeling - Zakaria Rugas; Almuntofa Purwantoro (Jurnal Basement : Jurnal Teknik Sipil, 2023)
The increasingly advanced development of the world of construction requires all parties involved in the project to complete construction projects effectively and efficiently. Prior to the existence of the building information modeling method, construction project planners used conventional methods with the help of AutoCAD software in planning project drawings, but this method was considered to be inefficient both in terms of time, quality and cost. One of the effective and efficient methods for planning is to use the Building Information Modeling method. The BIM method has advantages such as being able to save costs and time as well as costs because in the process this method allows planners to manage data with precision and detail in 3D modeling of buildings. This study aims to design a 3D structural model of the Poltekkes Building of Palangka Raya City, which is located on Jalan George Obos, Palangka Raya City. The data from this study are secondary data, namely detailed engineering design drawings. The results of the design of the structural model using the building information modeling method produce a structural model and detailed explanation in the form of a 3D model.